2015
DOI: 10.1515/cclm-2014-0929
|View full text |Cite
|
Sign up to set email alerts
|

First trimester concentrations of the TTR-RBP4-retinol complex components as early markers of insulin-treated gestational diabetes mellitus

Abstract: First trimester maternal serum ROH, RBP4 and TTR represent potential biomarkers associated with the development of iGDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
4
23
1
Order By: Relevance
“…Another case-control study found participants in the highest quartile of serum RBP4 had a 1.89 times higher risk of GDM compared with participants in the lowest quartile, while the relationship did not reach statistical significance after adjustment for maternal age, race, family history of diabetes, and pre-pregnancy overweight status [21]. However, Fruscalzo et al [9] found the concentrations of RBP4 in 11 insulin-treated GDM cases were significantly lower than 44 controls. Another research revealed an insignificant difference in serum concentrations of RBP4 between women who developed GDM and controls [22].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another case-control study found participants in the highest quartile of serum RBP4 had a 1.89 times higher risk of GDM compared with participants in the lowest quartile, while the relationship did not reach statistical significance after adjustment for maternal age, race, family history of diabetes, and pre-pregnancy overweight status [21]. However, Fruscalzo et al [9] found the concentrations of RBP4 in 11 insulin-treated GDM cases were significantly lower than 44 controls. Another research revealed an insignificant difference in serum concentrations of RBP4 between women who developed GDM and controls [22].…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis pooled results from 14 casecontrol studies reported that the serum RBP4 level was associated with the risk of GDM (pooled standardized mean difference = 0.816) [8]. Nevertheless, this metaanalysis only includes one article in the "before 24 weeks" subgroup and no association between serum RBP4 level and GDM risk was found [9]. Recently, a prospective study revealed that early pregnancy RBP4 concentrations were associated with increased risk of GDM [7].…”
Section: Introductionmentioning
confidence: 99%
“…These three peptides were demonstrated to be precursors of clusterin, isoform 1 of fibrinogen alpha chain and apolipoprotein CII[ 85 ]. Similarly, other studies using these novel techniques, have shown that glycosylated fibronectin[ 86 ] and the transthyretin-retinol binding protein-retinol complex[ 87 ] were early predictors of GDM, even before the onset of glucose intolerance.…”
Section: Etiology and Pathophysiology Of Gdmmentioning
confidence: 90%
“…More emphasis is placed on using interpretative, encouraging, persuasive language to explain relevant knowledge to patients and clarify their necessity. Relieve tension and fear, which helps patients actively cooperate with treatment [6][7]. Detailed patience expresses the necessity of surgery and the safety of the surgical procedure.…”
Section: Clinical Data and Methodsmentioning
confidence: 99%